Inversión privada, gasto público e impuestos en la Unión Europea; Private investment, government expenditure and taxes in the European Union - Luis Felipe Brito-Gaona; Emma M. Iglesias (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
– Using the same model that Caballero-Urdiales et al. (2012) and Brito-Gaona and Iglesias (2017) applied to Latin-American countries, we extend their analysis to the European Union (EU) in order to analyze the determinants of private investment. Results show consistent evidence with three hypotheses that, in some cases, are very different from those found in Latin America: First, both consumption and income taxes have significant effects on private investment, the same as happens in Latin America. Moreover, in the EU and Europe in general, corporate taxes are the lowest at worldwide level and much lower than in Latin America. We also find evidence in favor of the hypothesis that corporate income taxes do not affect private investment. Second, opposite to what happens in Latin America, public investment does not have significant effects on the evolution of private investment. And third, in order to stimulate private investment, government intervention has a negative effect, as happens in Latin America.
Keywords: F21; H24; H25; H54; 330; Private investment; gross domestic product; government ex- penditure; income tax; value-added tax